Exploration of Financial Statements CV. Wian Mandiri Based on Financial Accounting Standards for Micro, Small, and Medium Entities - Darmawan, Dimas Wahyu; Martiana, Nina; Probowulan, Diyah (Westscience Press, 2024)
The title of the research is